2005
DOI: 10.1073/pnas.0506769102
|View full text |Cite
|
Sign up to set email alerts
|

The B1-subunit of the H+ATPase is required for maximal urinary acidification

Abstract: The multisubunit vacuolar-type H ؉ ATPases mediate acidification of various intracellular organelles and in some tissues mediate H ؉ secretion across the plasma membrane. Mutations in the B1-subunit of the apical H ؉ ATPase that secretes protons in the distal nephron cause distal renal tubular acidosis in humans, a condition characterized by metabolic acidosis with an inappropriately alkaline urine. To examine the detailed cellular and organismal physiology resulting from this mutation, we have generated mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
163
3
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(183 citation statements)
references
References 25 publications
13
163
3
1
Order By: Relevance
“…37,38 Atp6v1b1 Ϫ/Ϫ mice demonstrated hypocalciuria, which is an important difference in phenotype between mice and humans with a genetic Atp6v1b1 defect, although it confirms previous observations of Finberg et al 38 The presence of hypocalciuria in Atp6v1b1 Ϫ/Ϫ has not been explained yet and needs further investigation. Moreover, Atp6v1b1…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…37,38 Atp6v1b1 Ϫ/Ϫ mice demonstrated hypocalciuria, which is an important difference in phenotype between mice and humans with a genetic Atp6v1b1 defect, although it confirms previous observations of Finberg et al 38 The presence of hypocalciuria in Atp6v1b1 Ϫ/Ϫ has not been explained yet and needs further investigation. Moreover, Atp6v1b1…”
Section: Discussionsupporting
confidence: 51%
“…38 Consequently, gene ablation of the Atp6v1b1 gene in TRPV5 Ϫ/Ϫ mice normalized urinary pH. Interestingly, TRPV5…”
Section: Discussionmentioning
confidence: 99%
“…If this is the case, then one would predict that Atp6v1b1 Ϫ/Ϫ animals should have a similar phenotype. Surprising, Atp6v1b1 Ϫ/Ϫ mice seem healthy, grow normally, do not have hearing defects, and are without systemic metabolic acidosis when on a normal diet and develop acidosis only when challenged (22,23). It is interesting that a recent study indicated that the absence of B1 expression induces a compensatory increase of the B2 isoform that potentially may act as a substitute isoform for B1 to increase H ϩ -ATPase activity in these Atp6v1b1 Ϫ/Ϫ mice (23).…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, we described how the exposure to high (5.0 mM) Ca 2ϩ concentrations significantly enhanced H ϩ -ATPase activity in CD cells (32). This stimulatory effect was absent in CD cells from Atp6v1b1 knockout mice that were genetically ablated for the CD-specific B1 subunit of H ϩ -ATPase (35). Moreover, the CaSR agonist neomycin increased H ϩ -ATPase activity as well, indicating the modulation of urinary acid excretion by CaSR activation.…”
Section: Casr Activation Decreases the Risk To Renal Stone Formation mentioning
confidence: 93%